Meeting the challenge of "America first" and the new nationalism. Issue 2 (3rd May 2020) - McCormick, James; Schmitz, Gerald
ABSTRACT: In this special issue, we outline some of the challenges that the Trump administration's foreign policy approach poses for Canada and the international system and bring together several distinguished academics, practitioners, and analysts who have begun to address these concerns. First, we outline the components of the "America First" nationalism of the Trump administration and identify some of its consequences for Canada and the larger global community. Next, we discuss how the "America First" approach is part of an emerging challenge to liberal democracy and to the long-standing liberal international order worldwide. With the increase in nationalism and populism globally and with the erosion of democratic commitment and practice by more and more states, Canada's traditional foreign policy of liberal internationalism is under increasing pressure to adapt and perhaps to change to maintain the global order. We have assembled a number of prominent scholars in this issue who offer important recommendations and prescriptions for the future direction of Canadian foreign policy.